Political Extremism According to Quassim Cassam - Kaluziński, Bartosz (Sensus Historiae, 2022)
In this paper I present and assess Quassim Cassam’s account of extremism. Cassam claims that there can be three basic types of accounts of extremism: ideological extremism, methods extremism, and psychological extremism, and the last one is probably the best. Cassam’s psychological account of extremism has some important advantages. First, it explains why some people are prone to very radical changes in their ideology. Second, it makes possible for a person with fairly mainstream ideology to be an extremist. Third, psychological account of extremism explains the possible discrepancy between one’s ideology and action: It is possible that a person with decidedly extreme beliefs does not resort to any extreme actions.